2023
DOI: 10.1002/msc.1748
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and its impact on prognosis following acute coronary syndrome or stroke: A linked electronic health record cohort study

Abstract: ObjectiveMusculoskeletal painful conditions are a risk factor for cardiovascular disease (CVD), but less is known about whether musculoskeletal pain also worsens prognosis from CVD. The objective was to determine whether patients with musculoskeletal pain have poorer prognosis following acute coronary syndrome (ACS) or stroke.MethodsThe study utilised UK electronic primary care records (CPRD Aurum) with linkage to hospital and mortality records. Patients aged ≥45 years admitted to hospital with incident ACS/st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…This is explained, in part, by being older, but in addition the observed associations seemed also to be explained by increased polypharmacy in patients with musculoskeletal pain. This is consistent with our previous study looking at short-term (30-day) outcomes in patients with a new ACS or stroke [ 32 ]. In the present study, we found that patients with musculoskeletal pain were being prescribed an average of 13–19 different medicines over 2 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is explained, in part, by being older, but in addition the observed associations seemed also to be explained by increased polypharmacy in patients with musculoskeletal pain. This is consistent with our previous study looking at short-term (30-day) outcomes in patients with a new ACS or stroke [ 32 ]. In the present study, we found that patients with musculoskeletal pain were being prescribed an average of 13–19 different medicines over 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…Derivation of code lists was based on those previously developed through a rigorous consensus approach in research studies by health-care practitioners, epidemiologists and statisticians with expertise in electronic health record research at Keele University [ 11 , 23 , 24 ] and code lists based on those from external studies using electronic health records. The code lists used for each index condition can be found at https://eprints.keele.ac.uk/id/eprint/11580/ [ 25 ]. The date of first diagnosis of the index condition was defined as the index date for that patient.…”
Section: Methodsmentioning
confidence: 99%